Complications in pregnant women with sickle cell disease - Smith-Whitley, Kim (Hematology Am Soc Hematol Educ Program, 2019)
Pregnancy in women with sickle cell disease (SCD) is associated with increased maternal and fetal morbidity and mortality. Outcomes vary widely owing to methodological limitations of clinical studies, but overall, hypertensive disorders of pregnancy, venothromboembolism, poor fetal growth, and maternal and perinatal mortality are increased globally. Few therapeutic interventions have been explored other than prophylactic and selective transfusion therapy. Unfortunately, existing data are limited, and it remains unclear whether prophylactic use of chronic transfusions will improve pregnancy outcomes. Management of pregnant women with SCD is best accomplished with a multidisciplinary team that includes a sickle cell expert and an obstetrician familiar with high-risk pregnancies. Women with SCD should have individualized care plans that outline management of acute pain and guidelines for transfusion therapy. Neonates require close monitoring for neonatal abstinence syndrome and hemolytic disease of the newborn. Ideally all young women with SCD will have a "reproductive life plan" developed as a component of preconception counseling and health promotion. Research leading to improved pregnancy management focused on diminishing adverse maternal and neonatal outcomes is overdue. International collaborations should be considered to improve subject recruitment and foster timely completion of clinical trials. Additional therapeutic interventions outside of transfusion therapy should be explored.